2023
DOI: 10.1093/rheumatology/kead321
|View full text |Cite
|
Sign up to set email alerts
|

A proteomics study of rheumatoid arthritis patients on etanercept identifies putative biomarkers associated with clinical outcome measures

Abstract: Objectives Biologic disease-modifying anti-rheumatic drugs (bDMARDs) are widely used in patients with rheumatoid arthritis (RA), but response to bDMARDs is heterogeneous. The objective of this work was to identify pre-treatment proteomic biomarkers associated with RA clinical outcome measures in patients starting bDMARDs. Methods Sequential Window Acquisition of all THeoretical fragment ion spectra mass spectrometry (SWATH-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“… 125 A more recent, much larger study used sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) in a study of 180 patients on etanercept therapy and identified proteins associated with treatment response. 132 Lower baseline levels of TCPH (Q99832) were associated with future remission and higher baseline levels of EHD1 (Q9H4M9) and TCPH (Q99832) were associated with DAS-28 score. In addition, lower baseline levels of SELENOP (P49908) and higher baseline levels of MAP2K3 (P46734) and CLTC (Q00610) were associated with hsCRP level at 6 months.…”
Section: Clinical Factors Predicting Drug Responsementioning
confidence: 91%
“… 125 A more recent, much larger study used sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) in a study of 180 patients on etanercept therapy and identified proteins associated with treatment response. 132 Lower baseline levels of TCPH (Q99832) were associated with future remission and higher baseline levels of EHD1 (Q9H4M9) and TCPH (Q99832) were associated with DAS-28 score. In addition, lower baseline levels of SELENOP (P49908) and higher baseline levels of MAP2K3 (P46734) and CLTC (Q00610) were associated with hsCRP level at 6 months.…”
Section: Clinical Factors Predicting Drug Responsementioning
confidence: 91%